Thermal and Photolytic Transformation of NHC–B, N‐Heterocycles: Controlled Generation of Blue Fluorescent 1, 3‐Azaborinine Derivatives and 1 H‐Imidazo[1, 2‐a]indoles by External Stimuli. Issue 40 (19th August 2015) - McDonald, Sean M.; Mellerup, Soren K.; Peng, Jinbao; Yang, Dengtao; Li, Quan‐Song; Wang, Suning
Abstract Invited for the cover of this issue are the groups of Suning Wang at the Queen's University (Canada) and Quan‐Song Li from Beijing Institute of Technology (P.R. China). The image depicts the unusual and distinct pathways of molecular transformation by N‐heterocyclic carbene bound B, N‐heterocycles. Read the full text of the article at 10.1002/chem.201502385.